ON SP-CONNECTED SPACES - KHALAF, ALIAS B.; SHAREEF, HARDI ALI (Science Journal of University of Zakho, 2013)
In this paper we introduce a new concept of connectedness namely Sp-connected space. This class of spaces is strictly between semi-connectedness and connectedness. Several properties and characterizations of this concept are found.
Keywords: semi-open sets; preclosed sets; semi-connected spaces; Sp-connected spaces